A study on optimization techniques for the sizing of DG in distribution system - Siti Rafidah, Abdul Rahim; Syahrul Asyikin, Azmi; Mohd Herwan, Sulaiman; Muhamad Hatta, Hussain; Siti Nor Baizura, Zawawi (Universiti Malaysia Perlis (UniMAP), 2011)
International Conference: Electrical Energy and Industrial Electronic Systems (EEIES 2009) organized by Universiti Malaysia Perlis (UniMAP), 7th - 8th December 2009 at Parkroyal Penang, Malaysia.